Change of the composition of splenic lymphocytes at the effect of argentogalactomanann and argento-poly-1-vinyl-1,2,4-triazole on the experimental animals - V. V. Voytkova; V. I. Dubrovina; S. A. Vityazeva; T. P. Starovoytova; K. M. Korytov; S. V. Balakhonov (Acta Biomedica Scientifica)
The article presents the results of the research of effect of metal-containing nanocomposites on the content of splenic Band T-lymphocytes of white mice. Phenotypic analysis of the spleen cells suspension was conducted by flow cytometry on BD FACSCanto ™ П. Stimulating effect of these medications on the immune response formation is showed and is proved by the increase of content of B-lymphocytes and T-helper cells and it indicates cooperative interactions between the cells of immune system. It was experimentally showed that the medications 2-N-HTP-Ag, GM-Ag can be recommended for the further research in order to increase protective properties of an organism.